2021
DOI: 10.1093/schbul/sbab037
|View full text |Cite
|
Sign up to set email alerts
|

Psychopathological Syndromes Across Affective and Psychotic Disorders Correlate With Gray Matter Volumes

Abstract: Introduction More than a century of research on the neurobiological underpinnings of major psychiatric disorders (major depressive disorder [MDD], bipolar disorder [BD], schizophrenia [SZ], and schizoaffective disorder [SZA]) has been unable to identify diagnostic markers. An alternative approach is to study dimensional psychopathological syndromes that cut across categorical diagnoses. The aim of the current study was to identify gray matter volume (GMV) correlates of transdiagnostic symptom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 90 publications
3
16
0
Order By: Relevance
“…Our findings are consistent with previous studies that demonstrated that MDD is a degenerative mental illness dominated by disrupted ReHo ( Späti et al, 2015 ) and GMV atrophy ( Schmaal et al, 2020 ; Zhang et al, 2020 ; Stein et al, 2021 ). By using ReHo and SCN analysis ( Lerch et al, 2006 ; Alexander-Bloch et al, 2013 ), we found that compared with healthy people, MDD patients had functional and structural defects in the CON and showed disrupted ReHo and GMV atrophy in the ACC.L and abnormal structural connectivity of the ACC.L–SFG.L ( Boes et al, 2018 ; Crowell et al, 2019 ; Cole et al, 2020 ; Rappaport et al, 2020 ).…”
Section: Discussionsupporting
confidence: 93%
“…Our findings are consistent with previous studies that demonstrated that MDD is a degenerative mental illness dominated by disrupted ReHo ( Späti et al, 2015 ) and GMV atrophy ( Schmaal et al, 2020 ; Zhang et al, 2020 ; Stein et al, 2021 ). By using ReHo and SCN analysis ( Lerch et al, 2006 ; Alexander-Bloch et al, 2013 ), we found that compared with healthy people, MDD patients had functional and structural defects in the CON and showed disrupted ReHo and GMV atrophy in the ACC.L and abnormal structural connectivity of the ACC.L–SFG.L ( Boes et al, 2018 ; Crowell et al, 2019 ; Cole et al, 2020 ; Rappaport et al, 2020 ).…”
Section: Discussionsupporting
confidence: 93%
“…A recent study found the associations between psychopathological syndromes and regional GMV across affective and psychotic disorders. Especially found positive formal thought disorder was correlated with the GMV of bilateral OFC (Stein et al, 2021). There was also a followup study in SZ that showed the important role of OFC in SZ.…”
Section: )mentioning
confidence: 88%
“…Given that mental disorders such as major depressive disorder (MDD), bipolar disorder (BD), and schizophrenia spectrum disorder (SSD) exhibit high overlap in many domains (e.g., psychopathology, genetics, neuropsychology, regional brain volume alterations), the research question has emerged whether they are characterized by more communalities rather than differences [1][2][3][4][5][6]. In the domain of brain morphometry, previous work has attempted, but failed, to find a unique neural correlate (i.e., biomarker) specific to one such disorder [2].…”
Section: Introductionmentioning
confidence: 99%
“…Since there is first evidence for significant GMV overlap across affective and psychotic disorders [2], it raises the question whether there are common, underlying factors that are responsible for these transdiagnostic findings. From previous structural brain imaging research, we know that the following four domains, among others, have been associated with brain structure in patients and healthy controls (HC): (1) early risk and protective factors: childhood maltreatment, urbanicity, familial risk, gestational age, birth weight, and parental bonding [12,[17][18][19][20], (2) current risk and protective factors: life events, resilience, and social support [21][22][23], (3) psychopathology: global functioning, positive, negative, depressive, and manic symptoms [3,24], and (4) neuropsychological performance [25]. To the best of our knowledge, it has not been investigated whether transdiagnostic morphometric alterations are related to transdiagnostic phenotypical or risk patterns.…”
Section: Introductionmentioning
confidence: 99%